Household Characteristics Factors and Drinking Water Sources in Urban Nigerian Communities: A Cross-Sectional Study - Dyah Suryani; Suyitno; Abubakar Yakubu Abbani (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Environmental health remains a problem, particularly regarding access to drinking water in developing countries. This study aimed to examine the correlation of household characteristics and drinking water sources in urban communities in Nigeria. Methods: A cross-sectional study was conducted using data from the Nigeria Demographic and Health Survey (NDHS), with 42,859 urban household members. The variables used were drinking water sources, sex and age of household head, education level, wealth index, religion, relationship to household head, presence of children under five, and household size. Data were analyzed using descriptive, bivariate, and logistic regression analyses. Results and Discussion: The majority of households (88.13%) used improved drinking water sources. Older, more educated, wealthier, and smaller households, including female-headed households and households without small children, have better access to clean water. The wealth index was the strongest predictor: middle, richer, and richest households were significantly less likely to use untreated water than the poorest households (p < 0.001). Older household heads were less likely to rely on untreated water (p < 0.05). Secondary-level education, religion, and household size were also significant (p < 0.001). These results highlight inequalities in accessing safe water, influenced by economic, demographic, and cultural factors. Conclusion: These results suggest focused solutions to support younger household heads, make water systems more affordable, and reach disadvantaged neighborhoods. Pro-poor water policies and equitable infrastructure are key to reducing disparities in access to clean drinking water